2014
DOI: 10.1182/blood-2013-07-515361
|View full text |Cite
|
Sign up to set email alerts
|

Bruton’s tyrosine kinase (BTK) function is important to the development and expansion of chronic lymphocytic leukemia (CLL)

Abstract: Chronic lymphocytic leukemia (CLL) is characterized by constitutive activation of the B-cell receptor (BCR) signaling pathway, but variable responsiveness of the BCR to antigen ligation. Bruton's tyrosine kinase (BTK) shows constitutive activity in CLL and is the target of irreversible inhibition by ibrutinib, an orally bioavailable kinase inhibitor that has shown outstanding activity in CLL. Early clinical results in CLL with other reversible and irreversible BTK inhibitors have been less promising, however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
171
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 191 publications
(174 citation statements)
references
References 28 publications
(42 reference statements)
3
171
0
Order By: Relevance
“…Another tyrosine kinase that is uniformly overexpressed and constitutively active in CLL is Bruton's tyrosine kinase (BTK; refs. [29][30][31]. Here, using an antibody that cross-reacts with phosphorylated (p) ZAP-70 and p-Syk ( 32 ), we showed substantially enhanced expression of p-ZAP-70/Syk in Eμ-Tcl1 leukemia cells compared with B lymphocytes.…”
Section: Fob Cells Eμ-tcl1 Fob Cells Eμ-tcl1mentioning
confidence: 99%
“…Another tyrosine kinase that is uniformly overexpressed and constitutively active in CLL is Bruton's tyrosine kinase (BTK; refs. [29][30][31]. Here, using an antibody that cross-reacts with phosphorylated (p) ZAP-70 and p-Syk ( 32 ), we showed substantially enhanced expression of p-ZAP-70/Syk in Eμ-Tcl1 leukemia cells compared with B lymphocytes.…”
Section: Fob Cells Eμ-tcl1 Fob Cells Eμ-tcl1mentioning
confidence: 99%
“…1 cells were obtained from spleens of TCL1 transgenic mice with CLLlike leukemia and splenomegaly, and 1 3 10 6 cells were injected intravenously into a C57BL/6 mouse as previously described 37 and specified in the supplemental Methods.…”
Section: Cd19mentioning
confidence: 99%
“…However, so far the molecular consequence of silencing of BCR-ABL has not been studied systematically. The previous studies showed that chemically synthesized siRNA specifically silenced the target gene (Woyach et al, 2013;Woyach et al, 2013). This study was performed on BCR-ABL in K562 cell.…”
Section: Discussionmentioning
confidence: 99%
“…Since the ground-breaking discovery that double-stranded RNA molecules 21-23 nucleotides in length, named small interfering RNAs (siRNAs), are able to elicit gene-specific inhibition also in mammalian cells, the interest of the scientific community has rapidly been drawn to the potential of these siRNAs for targeting oncogenic fusion genes in leukaemic cells (Ramakrishnan et al, 2014). There has been a flurry of reports describing overexpressed or mutated genes that may also serve as attractive targets for therapeutic intervention by RNA silencing methods (Woyach et al, 2013;.…”
Section: Introductionmentioning
confidence: 99%